Combinatorial chemistry in nematodes: modular assembly of primary metabolism-derived building blocks - von Reuss, Stephan H. (Nat Prod Rep, 2015)
The nematode Caenorhabditis elegans was the first animal to have its genome fully sequenced and has become an important model organism for biomedical research. However, like many other animal model systems, its metabolome remained largely uncharacterized, until recent investigations demonstrated the importance of small molecule-based signalling cascades for virtually every aspect of nematode biology. These studies have revealed that nematodes are amazingly skilled chemists: using simple building blocks from conserved primary metabolism and a strategy of modular assembly, C. elegans and other nematode species create complex molecular architectures to regulate their development and behaviour. These nematode-derived modular metabolites (NDMMs) are based on the dideoxysugars ascarylose or paratose, which serve as scaffolds for attachment of moieties from lipid, amino acid, carbohydrate, citrate, and nucleoside metabolism. Mutant screens and comparative metabolomics based on NMR spectroscopy and MS have so-far revealed several 100 different ascarylose (“ascarosides”) and a few paratose (“paratosides”) derivatives, many of which represent potent signalling molecules that can be active at femtomolar levels, regulating development, behaviour, body shape, and many other life history traits. NDMM biosynthesis appears to be carefully regulated as assembly of different modules proceeds with very high specificity. Preliminary biosynthetic studies have confirmed the primary metabolism origin of some NDMM building blocks, whereas the mechanisms that underlie their highly specific assembly are not understood. Considering their functions and biosynthetic origin, NDMMs represent a new class of natural products that cannot easily be classified as “primary” or “secondary”. We believe that the identification of new variants of primary metabolism-derived structures that serve important signalling functions in C. elegans and other nematodes provides a strong incentive for a comprehensive re-analysis of metabolism in higher animals, including humans.